Activation of PKA via asymmetric allosteric coupling of structurally conserved cyclic nucleotide binding domains - Yuxin Hao (Nature Portfolio, 2019)
Protein kinase A (PKA) is a cyclic nucleotide dependent protein kinase. Here the authors use single molecule optical tweezers and steered molecular dynamic simulations to follow in real time and quantitatively characterize the signals transduced by cAMP through the structure of the PKA regulatory subunit, and propose a model for PKA allosteric activation.